Effects of machining methods on uniaxial tensile properties of 75μm thick 304L stainless steel foil (Fracture and Structural Integrity, 2026)
Considering the fragility of ultra-thin foil material, the machining methods might bring in undesired and non-neglectable damage, which would affect the uniaxial tensile properties of such material. This presented work systematically investigates the effect of five machining methods on the tensile performance of 75μm thick 304L stainless steel foil across four different gage width through uniaxial tension test. The yield stress and ultimate strength are found insensitive to the machining methods and gage widths. Full-field digital image correlation analysis confirmed that the fabrication method dictates the failure mode. Laser cutting and photochemical etched specimens failed in the gage central portion due to intrinsic plastic instability, while specimens fabricated by electrical discharge machining, mechanical milling, and waterjet cutting failed prematurely from process-induced edge defects. Thus, the uniform and fracture elongations were dependent on the process. Geometric size effect on material ductility was also observed for samples with good or moderate edge qualities.
Keywords: 304L stainless steel foil; Machining methods; Edge defect; Digital image correlation; Failure mode